(untitled) (Research, Society and Development, 2020)
Violence is present in today’s society and seems to contribute to the occurrence of hypertensive crises. The aim of this study is to describe the perception of the user of primary health care about this association (violence and hypertensive crises). Descriptive study carried out with hypertensive adults in the area enrolled in a Primary Health Care Unit in Fortaleza-Ceará, with semi-structured interviews in the year 2018. The reports were transcribed in full and Bardin’s Categorical Analysis was carried out. Four units of meaning were defined: 1- perceived feelings and hypertensive crises; 2- violence and hypertensive crises; 3- family conflict and hypertensive crises; 4- change in the social context and hypertensive crises. The findings showed that when hypertensive residents of violent areas witness and experience situations of violence, this triggers the crisis, sometimes perceived by different symptoms, sometimes by checking blood pressure. It is concluded that many of the cases were actually hypertensive pseudocrisis and that the distinction between them requires the skill of the multidisciplinary team, as they are at odds in the approach.